2019
DOI: 10.1016/j.ebiom.2019.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Benzene metabolites trigger pyroptosis and contribute to haematotoxicity via TET2 directly regulating the Aim2/Casp1 pathway

Abstract: BackgroundLong term low-dose benzene exposure leads to the inhibition of haematopoiesis. However, the underlying mechanisms remained poorly defined, especially mediated by early effector molecules.MethodsHere, we first found in mRNA microarray that pyroptotic classic genes (Casp1, 4, 5, and IL1β) were up-regulated and represented dose-dependent differential expression in controls, low-dose benzene-exposed and chronic benzene-poisoned workers, and the expression of Casp1 and IL1β were confirmed in low-dose benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 32 publications
0
8
0
2
Order By: Relevance
“…Recent epidemiological studies have shown that global acute myelocytic leukemia (AML) morbidity and mortality have been increasing over the past 28 years and that occupational exposure to benzene is considered a major risk factor ( 1 ). According to the latest report from the National Bureau of Statistics, China’s pure benzene output has been increasing year after year, which may partly explain why the benzene poisoning and leukemia cases have remained high in recent years ( 2 ). Previous studies have shown that workers exposed to 1 ppm benzene exhibited no substantial WBC harm, but their BM hematopoietic capability was severely reduced in terms of renewal and differentiation ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological studies have shown that global acute myelocytic leukemia (AML) morbidity and mortality have been increasing over the past 28 years and that occupational exposure to benzene is considered a major risk factor ( 1 ). According to the latest report from the National Bureau of Statistics, China’s pure benzene output has been increasing year after year, which may partly explain why the benzene poisoning and leukemia cases have remained high in recent years ( 2 ). Previous studies have shown that workers exposed to 1 ppm benzene exhibited no substantial WBC harm, but their BM hematopoietic capability was severely reduced in terms of renewal and differentiation ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been discovered that inflammation mediated by a specific intracellular signaling platform (the NLRP3 inflammasome) that self-assembles in the cytosol of immune cells in response to exposures above an activation threshold (Cox 2019) drives the pathogenesis of MDS (Sallman and List 2019). Recent findings that benzene induces inflammatory programmed cell death (pyroptosis) (Sallman et al 2016;Guo et al 2019) and autophagy (Qian et al 2019) underscore the importance of inflammatory responses in benzene-induced pathogenesis. Although inflammation increases ROS and oxidative stress and cell turnover, thus potentially increasing formation and proliferation of HSCs with unrepaired cytogenetic damage and chromosomal aberrations, the inflammatory MoA suggests that it is the underlying inflammation that drives health risks.…”
Section: Benzene Health Effects and Hypothesized Causal Biological Mechanismsmentioning
confidence: 99%
“…Listadas na Tabela 1 (OSÓRIO, 2018). desenvolver anestesia do sistema nervoso central e falência de órgãos, enquanto as exposições a longo prazo em baixas doses causam diminuição na contagem de células sanguíneas periféricas, envenenamento crônico por benzeno e até neoplasias hematológicas como SMD e leucemia, além de mutações cromossômicas (GUO et al, 2019). [300] A biorremediação é um processo que utiliza principalmente microrganismos, plantas, enzimas microbianas ou vegetais para desintoxicar e degradar contaminantes no solo e em outros ambientes, com a finalidade de restaurar a saúde do ecossistema (GOUMA et al, 2014).…”
Section: Hidrocarbonetos De Cadeia Monoaromáticaunclassified